New mathematical cuneiform texts - Friberg, Jöran (Sources and studies in the history of mathematics and physical sciences, 2016)
Preface -- Contents -- 1. Late Babylonian Tables of Many-Place Regular Sexagesimal Numbers, from Babylon, Sippar, and Uruk -- 1.1 Late Babylonian Texts Concerned with Many-Place Regular Sexagesimal Numbers -- 1.2 Table B (Babylon). Fragments of a Seleucid Many-Place Table of Reciprocals, with n from 1 to 2 -- 1.2.1 BM 35568. A List of Squares of Many-Place Regular Sexagesimal Numbers -- 1.2.2 Attested Many-Place Regular Numbers n in the Fragments and in Tables U and S -- 1.2.3 Table R: A Reconstructed Common Ancestor to Tables B, U, and S -- 1.2.4 The Numerical Algorithms Used for the Construction of Table R -- 1.2.5 The Double 6-Place Hexagon and the 12-Place Flower in the Index Grid -- 1.2.6 An Error in a Table of Squares Related to the Enlarged Table B* -- 1.3 Table U = W 23283+22905 (Uruk). An Achaemenid Many-Place Table of Reciprocals, with n from 1 to 4 -- 1.3.1 Mathematical and Metrological Tablets from a House in Achaemenid Uruk -- 1.3.2 A Curious Incipit, and a Colophon -- 1.3.3 A Curious Use of the Technical Term íb.si in Table U -- 1.3.4 Numerical Errors in Table U -- 1.3.5 A Curious Extra Line in Table U -- 1.3.6 Table U. New Photos and Transliterations -- 1.4 Table S = Sippar 2175/12. A Neo-Babylonian Many-Place Table of Reciprocals, with n f rom 1 to 3 -- 1.4.1 Numerical Errors and Missing Pairs in Table S -- 1.4.2 Table S. Hand Copies and Conform Transliterations -- 1.5 Table V = AO 6456 (Uruk). A Seleucid Many-Place Table of Reciprocals, with n from 1 to 3 -- 1.5.1 An Invocation, a Many-Place Table of Reciprocals, a Description, and a Colophon -- 1.5.2 Numerical Errors and Missing Pairs in Table V -- 1.5.3 Representation in the Index Grid, Inside a 6-place Double Triangle -- 1.5.4 Table U. New Photos -- 1.6 Table W = W 23281, rev. (Uruk). An Atypical Achaemenid Many-Place Table of Reciprocals